Photo-thermal auxiliary oil recovery aerogel as well as preparation method and application thereof

The photothermal auxiliary oil recovery aerogel prepared by thermosensitive methylcellulose and MXene composites solves the problems of low absorption capacity and poor recycling in the oil recovery process of existing adsorbent materials, and achieves high quality The rapid adsorption and self-contraction recovery of viscosity oil are suitable for a variety of oil treatments.

CN119236899APending Publication Date: 2025-01-03ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411529933.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing adsorbent materials have low absorption capacity, poor recycling ability during the oil recovery process, and complex recycling methods, making it difficult to effectively deal with high viscosity oils and different oil products.

Method used

The thermosensitive methylcellulose and MXene composite materials are used to prepare aerogel for photothermal auxiliary oil recovery, and the rapid adsorption and self-contraction recovery of oil products are achieved through photothermal effect.

Benefits of technology

This aerogel has excellent mechanical properties and photothermal properties, and can quickly adsorb high viscosity oil under light conditions and achieve self-contraction recovery, simplifying the process and is suitable for industrial waste oil, sewage and offshore oil spill treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236899A_ABST
    Figure CN119236899A_ABST
Patent Text Reader

Abstract

The invention discloses photo-thermal auxiliary oil recovery aerogel and a preparation method and application thereof, and the preparation method comprises the following specific steps: embedding methyl cellulose as a main matrix into a polyhydroxy polymer cross-linked network, and preparing thermal response mechanism aerogel through a freeze drying method. Then MXene is introduced into the aerogel through a soaking method, and finally the photo-thermal auxiliary oil product recovery aerogel is obtained. Due to the introduction of the methyl cellulose with thermosensitivity, the polyhydroxy cross-linked network has a thermal induction effect, and the volume shrinkage of the aerogel is initiated through the photothermal conversion of MXene under an illumination condition, so that the efficient absorption and recovery of an oil product are realized. The prepared aerogel can quickly adsorb high-viscosity oil under light and heat and recover the adsorbed oil through self-contraction, has excellent mechanical performance and light and heat performance, and has wide application prospects in the field of oil product absorption and recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photothermal material preparation, and specifically relates to a photothermal-assisted oil recovery aerogel and a preparation method and application thereof. Background Art

[0002] With the development of industry, oil spills and industrial organic solvent discharge accidents occur frequently, posing a major threat to the ecological environment and human society. For example, the Deepwater Horizon and Exxon Valdez oil spills in the Gulf of Mexico caused great harm to the local marine and coastal ecosystems. Therefore, various traditional adsorbent materials such as natural fibers, expanded graphite, organic polymers, and activated carbon have been used for oil spill and organic solvent treatment. However, low absorption capacity and poor recyclability are still a problem to be solved for oily wastewater purification and oil recovery.

[0003] In recent years, three-dimensional porous materials are beneficial for collecting various oils and organic solvents from oil-water mixtures due to their excellent adsorption properties, high porosity, and interconnected network structure. Su et al. [Su C, Yang H, Zhao H, et al. Chemical Engineering Journal, 2017, 330: 423-432.] prepared chitosan sponges by crosslinking sodium triphosphate and citral and modifying with octadecanethiol. The sponges have good mechanical properties and high porosity, can selectively remove emulsified oil from water, and can still maintain high absorption capacity and excellent separation performance after multiple recycling. Wang et al. [Wang X, Liu Z, Liu X, et al. Carbon, 2022, 193: 77-87.] prepared polyvinylidene fluoride / silicon dioxide @ graphene oxide aerogels by electrospinning and freeze drying. The aerogels have an interactive fiber three-dimensional skeleton structure, good hydrophobicity and excellent mechanical properties, and can achieve continuous oil-water separation under the drive of a peristaltic pump. Although these adsorbent materials have good adsorption properties for oil and organic solvents, the way to recover oil is still limited to mechanical compression, pumping devices or electrocapillary suction, which not only destroys the properties of the material itself and leads to a decrease in adsorption performance, but also involves complex processes and specific equipment in practical applications. Therefore, the development of intelligent oil-absorbing materials with controllable adsorption and desorption capabilities has become an urgent need for oil spill cleanup and recovery. Summary of the invention

[0004] The purpose of the present invention is to provide a photothermal assisted oil recovery aerogel and its preparation method and application. The preparation method is simple and easy, the raw material source is wide, and it has good performance in high viscosity oil adsorption and different oil recovery.

[0005] In view of the above problems, the present invention adopts thermosensitive methyl cellulose as the main matrix and composites MXene photothermal material to finally obtain a photothermal-assisted oil recovery aerogel. The introduction of methyl cellulose makes the polyhydroxy cross-linked network have a thermal induction effect, and the aerogel itself shrinks in volume under light conditions through MXene photothermal conversion, thereby realizing efficient recovery of oil. The aerogel can quickly adsorb high-viscosity oil and self-shrink to recover the adsorbed oil under photothermal conditions, has excellent mechanical properties and photothermal properties, and has broad application prospects in the field of oil absorption and recovery.

[0006] The present invention proposes a method for preparing a photothermal-assisted oil recovery aerogel, and the technical scheme adopted is as follows:

[0007] A method for preparing a photothermal-assisted oil recovery aerogel. The present invention prepares a thermally-induced volume-shrinking methyl cellulose aerogel by cross-linking methyl cellulose and a polyhydroxy polymer, and composites MXene on the aerogel by an immersion method, and finally obtains a photothermal-assisted oil recovery aerogel. The introduction of methyl cellulose gives the polyhydroxy cross-linked network a thermal induction effect, triggering its own volume shrinkage, thereby achieving efficient recovery of oil. The preparation method of the present invention has easy-to-obtain raw materials and strong operability. It has a wide range of application value in industrial waste oil recovery, sewage treatment, and offshore oil spill recovery and treatment. The specific steps are as follows:

[0008] (1) adding an aqueous solution of 2.5%-17.5% by mass of methyl cellulose and 2%-20% by mass of a polyhydroxy polymer into a beaker, and then adding an appropriate amount of deionized water, stirring for 1-3 hours to obtain a mixed solution of the polyhydroxy polymer and methyl cellulose, wherein the mass ratio of methyl cellulose, polyhydroxy polymer and deionized water is 1:1-4:300-2000;

[0009] (2) adjusting the pH value of the mixed solution in (1), then adding a certain amount of a cross-linking agent, and stirring for 1-4 hours to obtain a cross-linked solution;

[0010] (3) The cross-linked solution in (2) is transferred to a mold and placed in a refrigerator at -25°C to -15°C for freezing, and then freeze-dried at -45°C to -55°C for 27 to 37 hours (more preferably, placed in a refrigerator at -20°C for freezing and freeze-dried at -50°C for 32 hours) to obtain a methylcellulose porous material.

[0011] (4) The porous material obtained in (3) is immersed in an aqueous dispersion of MXene, and allowed to stand for 10-40 minutes. After being completely absorbed, it is placed in a refrigerator at -25°C to -15°C for freezing, and then freeze-dried at -45°C to -55°C for 20 to 28 hours (more preferably, placed in a refrigerator at -20°C for freezing, and freeze-dried at -50°C for 24 hours), to finally obtain an aerogel material for photothermal-assisted oil recovery.

[0012] The polyhydroxy polymer in step (1) is one or more of polyvinyl alcohol, polyethylene glycol, polypropylene alcohol, polysaccharide, or cellulose;

[0013] The pH value in step (2) is in the range of 1-11 (more preferably 2-11), the cross-linking agent is one or more of glutaraldehyde, formaldehyde, citral or terephthalaldehyde, and the mass ratio of the cross-linking agent to methylcellulose is 2.5-12:1;

[0014] The concentration of the aqueous dispersion of MXene in step (4) is 1-10 mg / mL.

[0015] The MXene (Ti3C2T X ) The preparation process is as follows:

[0016] 3.2g lithium fluoride was dissolved in 25mL hydrochloric acid solution (12M HCI plus water to 40mL), and then stirred at room temperature for 15 minutes; the temperature was raised to 42°C, 2.0g Ti3AlC2 was slowly added, and the mixture was stirred continuously for 48 hours in an oil bath at 42°C; after the reaction, the etching solution was poured into a centrifuge tube, shaken and centrifuged at 5000rpm for 2min; the supernatant was poured out, and then deionized water was added to the centrifuge tube, shaken, and then centrifuged and washed several times to obtain a neutral solution; in a nitrogen atmosphere, bubbled for 2-3min, and ultrasonicated for 1h in an ice bath; the ultrasonicated solution was centrifuged at 3500rpm for 20min, and the supernatant was collected as a single-layer MXene solution. The single-layer MXene solution was filtered and dried to finally obtain MXene (Ti3C2T X ).

[0017] The invention discloses an application of a method for preparing a photothermal-assisted oil recovery aerogel in high-viscosity oil absorption.

[0018] The preparation method of the photothermal-assisted oil recovery aerogel prepared by the present invention is applied in oil absorption and recovery.

[0019] The photothermal-assisted oil recovery aerogel prepared by the present invention has the following beneficial effects:

[0020] a. The preparation process of the present invention is simple, the raw materials are widely available, and it is easy to produce on a large scale;

[0021] b. Through chemical cross-linking, the prepared photothermal assisted oil recovery aerogel has good mechanical properties and is easy to transport;

[0022] c. The aerogel has a high photothermal effect and can achieve rapid absorption of high-viscosity oil;

[0023] d. Excellent photothermal performance. The prepared aerogel can shrink in volume under light, thereby achieving the purpose of oil absorption and recovery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The following is a further detailed description of the implementation method of the present invention in conjunction with the accompanying drawings.

[0025] Figure 1 (a) The cross-linking mechanism of methyl cellulose and polyhydroxy polymer, (b) Schematic diagram of the process of preparing a photothermal-assisted oil recovery aerogel;

[0026] Figure 2 (ac) are scanning electron micrographs of the prepared aerogel surface at different magnifications;

[0027] Figure 3 (a) Reversible compression image of the prepared aerogel, (b) stress-strain curves at 30%, 40%, 50%, and 60% compressive strain, and (c) cyclic stress-strain curve at 40% compressive strain;

[0028] Figure 4 The surface temperature of the prepared aerogel changes under different light intensities;

[0029] Figure 5 are images of the prepared aerogel absorbing crude oil under (a) no light source or (b) light source;

[0030] Figure 6 (a) is the recovery image of dodecane and soybean oil of the prepared aerogel and comparative example 1 under illumination, (bc) is the volume of comparative example 1 and the prepared aerogel before and after illumination;

[0031] Figure 7 (ac) are scanning electron microscope images of comparative example 1. DETAILED DESCRIPTION

[0032] The present invention is further described below by means of specific examples, but the protection scope of the present invention is not limited thereto.

[0033] Embodiment 1:

[0034] A method for preparing a photothermal assisted oil recovery aerogel (the preparation process is shown in the following figure) Figure 1 As shown), comprising the following process steps:

[0035] (1) 7.5 wt % methyl cellulose (methyl cellulose, viscosity 15 mPa s) aqueous solution and 14 wt % polyvinyl alcohol (1799 type, alcoholysis degree 98-99% (mol / mol)) aqueous solution were added into a beaker in sequence, the mass ratio of methyl cellulose, polyvinyl alcohol and deionized water was 1:2:650, and stirred for 1 h;

[0036] (2) adjusting the pH value of the mixed solution in (1) to 2, adding glutaraldehyde, and reacting at room temperature of 25° C. for 1 h to carry out aldol condensation;

[0037] The mass ratio of methylcellulose to glutaraldehyde is 1:5;

[0038] (3) transferring the reaction solution in (2) into a mold, freezing it in a refrigerator at -20°C, and freeze-drying it at -50°C for 32 hours to obtain a methylcellulose porous material;

[0039] (4) The porous material in (3) was immersed in a MXene aqueous solution with a concentration of 1 mg / mL, and allowed to stand for 30 min. After being completely absorbed, the material was placed in a -20°C refrigerator for freezing, and freeze-dried at -50°C for 24 hours to obtain an aerogel material for photothermal-assisted oil recovery.

[0040] The scanning electron microscopy image of the prepared aerogel is shown in Figure 2 (ac) as shown;

[0041] (a) Reversible compression image of the prepared aerogel, (b) stress-strain curves at 30%, 40%, 50%, and 60% compressive strain, (c) cyclic stress-strain curve at 40% compressive strain. Figure 3 As shown;

[0042] The surface temperature of the prepared aerogel changes under different light intensities. Figure 4 As shown;

[0043] The images of the prepared aerogel absorbing crude oil without light source (a) or with light source (b) are shown in Figure 2. Figure 5 As shown;

[0044] The prepared aerogel and comparative example 1 (a) are images of the recovery of low-viscosity oil dodecane and high-viscosity soybean oil under light, and (bc) are the volumes of comparative example 1 and photothermal-assisted oil recovery aerogel before and after light irradiation. Figure 6 shown.

[0045] Embodiment 2:

[0046] A method for preparing a photothermal assisted oil recovery aerogel (the preparation process is shown in the following figure) Figure 1 As shown), comprising the following process steps:

[0047] (1) Add 2.5 wt % methyl cellulose aqueous solution and 2 wt % polyethylene glycol aqueous solution into a beaker in sequence, with the mass ratio of methyl cellulose, polyethylene glycol and deionized water being 1:1:500, and stir for 1 h;

[0048] (2) adjusting the pH value of the mixed solution in (1) to about 7, adding formaldehyde, and reacting at room temperature of 25° C. for 1 h to carry out aldol condensation;

[0049] The mass ratio of formaldehyde to methyl cellulose is 2.5:1;

[0050] (3) transferring the reaction solution in (2) into a mold, freezing it in a refrigerator at -20°C, and freeze-drying it at -50°C for 32 hours to obtain a methylcellulose porous material;

[0051] (4) The porous material in (3) was immersed in a MXene aqueous solution with a concentration of 2 mg / mL, and allowed to stand for 30 min. After being completely absorbed, the material was placed in a -20°C refrigerator for freezing, and freeze-dried at -50°C for 24 hours to obtain an aerogel material for photothermal-assisted oil recovery.

[0052] Embodiment 3:

[0053] A method for preparing a photothermal assisted oil recovery aerogel (the preparation process is shown in the following figure) Figure 1 As shown), comprising the following process steps:

[0054] (1) Add 12.5 wt % methyl cellulose aqueous solution and 8 wt % polyacryl alcohol aqueous solution into a beaker in sequence, with the mass ratio of methyl cellulose, polyacryl alcohol and deionized water being 1:3:800, and stir for 1 h;

[0055] (2) adjusting the pH value of the mixed solution in (1) to about 9, adding citral, and reacting at room temperature of 25° C. for 1 h to carry out aldol condensation;

[0056] The mass ratio of citral to methylcellulose is 11:1;

[0057] (3) transferring the reaction solution in (2) into a mold, freezing it in a refrigerator at -20°C, and freeze-drying it at -50°C for 32 hours to obtain a methylcellulose porous material;

[0058] (4) The porous material in (3) was immersed in a MXene aqueous solution with a concentration of 3 mg / mL, and allowed to stand for 30 min. After being completely absorbed, the material was placed in a -20°C refrigerator for freezing, and freeze-dried at -50°C for 24 hours to obtain an aerogel material for photothermal-assisted oil recovery.

[0059] Comparative Example 1:

[0060] (1) 7.5 wt% methyl cellulose and 14 wt% polyvinyl alcohol aqueous solution were added into a beaker in sequence, with the mass ratio of methyl cellulose, polyvinyl alcohol and water being 1:2:650, and stirred for 1 h;

[0061] (2) adjusting the pH value of the reaction solution in (1) to about 2, adding glutaraldehyde, and carrying out aldol condensation at room temperature for 1 hour;

[0062] The mass ratio of glutaraldehyde to methyl cellulose is 5:1;

[0063] (3) then transferring the reaction solution in (2) into a mold and freezing it in a refrigerator at -20°C, and freeze-drying it at -50°C for 32 hours to obtain a methylcellulose porous material;

[0064] The scanning electron microscope image of the prepared methyl cellulose porous material is as follows: Figure 7 (ac) as shown;

[0065] The above embodiments are not limitations of the present invention, and the present invention is not limited to the above embodiments. As long as the requirements of the present invention are met, they belong to the protection scope of the present invention.

Claims

1. A method for preparing a photothermal assisted oil recovery aerogel, characterized in that: The steps include: (1) adding a methylcellulose aqueous solution and a polyhydroxy polymer aqueous solution into a container, then adding deionized water and stirring to obtain a mixed solution of the polyhydroxy polymer and methylcellulose; (2) adjusting the pH value of the mixed solution in (1), then adding a crosslinking agent and stirring to obtain a crosslinked solution; (3) transferring the cross-linked solution in (2) into a mold, freezing it in a refrigerator, and then freeze-drying it to obtain a methylcellulose porous material; (4) Immerse the methyl cellulose porous material obtained in (3) into the aqueous dispersion of MXene, let it stand for 10-40 minutes, and put it into a refrigerator to freeze after it is completely absorbed, and then freeze-dry it to finally obtain a photothermal-assisted oil recovery aerogel.

2. The method for preparing the photothermal assisted oil recovery aerogel according to claim 1, characterized in that: In step (1), the mass fraction of methyl cellulose in the methyl cellulose aqueous solution is 2.5-17.5%; The mass fraction of the polyhydroxy polymer in the polyhydroxy polymer aqueous solution is 2-20%; The mass ratio of the methyl cellulose, the polyhydroxy polymer and the deionized water is 1:1-4:300-2000.

3. The method for preparing the photothermal assisted oil recovery aerogel according to claim 1, characterized in that: In step (1), the polyhydroxy polymer is one or more of polyvinyl alcohol, polyethylene glycol, and polypropylene alcohol.

4. The method for preparing the photothermal assisted oil recovery aerogel according to claim 1, characterized in that: In step (1), stirring for 1-3 hours; In step (2), stirring is performed for 1-4 hours.

5. The method for preparing the photothermal assisted oil recovery aerogel according to claim 1, characterized in that: In step (2), the pH value ranges from 1 to 11.

6. The method for preparing the photothermal assisted oil recovery aerogel according to claim 1, characterized in that: In step (2), the cross-linking agent is one or more of glutaraldehyde, formaldehyde, citral, and terephthalaldehyde; The mass ratio of the methyl cellulose to the cross-linking agent is 1:2.5-12.

7. The method for preparing the photothermal assisted oil recovery aerogel according to claim 1, characterized in that: In step (3), the mixture is placed in a refrigerator at -25°C to -15°C and then freeze-dried at -45°C to -55°C for 27 to 37 hours; In step (4), the mixture is allowed to stand for 10-40 minutes, and after being completely absorbed, the mixture is placed in a -25°C to -15°C refrigerator for freezing, and then freeze-dried at -45°C to -55°C for 20-28 hours.

8. The method for preparing the photothermal assisted oil recovery aerogel according to claim 1, characterized in that: In step (4), the concentration of the aqueous dispersion of MXene is 1-10 mg / mL.

9. Photothermal-assisted oil recovery aerogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the photothermal assisted oil recovery aerogel as claimed in claim 9 in oil absorption and recovery.